Quaternary Ammonium based Eutectic Ionic Liquids (EILs) as absorbent for Sulfur Dioxide (SO2) - Chandran, K. (Institute of Physics Publishing, 2020)
Sulfur dioxide (SO2) is a corrosive acid gas which pose severe threat to the environment and human health. Therefore, its removal from air is necessary to protect human health and environmental quality. Existing SO2 removal technologies involves using lime or limestone in wet scrubbers. Recently, the application of eutectic ionic liquids (EILs) were extensively employed to capture SO2 gases. The main objective of this study is to determine the SO2 absorption capacities of quaternary ammonium based EILs. Quaternary ammonium- based EIL, choline chloride which is known to display many advantages in absorbing acidic gas, were selected as the hydrogen bond acceptor (HBA) and three different types of hydrogen bond donor (HBD) were investigated; glycerol, ethylene glycol, and urea. The absorption experiments were conducted in a laboratory scale reactor. SO2 gas stream was passed continuously through the reactor to get contact with the EIL surface and be absorbed, and the absorption was monitored using sodium hydroxide (NaOH) solution with pH 10. The results show that SO2 was absorbed by choline chloride (ChCl) based EILs within 120 min of contact time. The absorption capacity of ChCl with glycerol was 0.54 mg/g, 0.54 mg/g and 0.53 mg/g for 1:2, 1:3 and 1:4, respectively. The results also show that the SO2 absorption capacity increases as the ChCl:Gly molar ratio increases. The extent of absorption was also greatly affected by the composition of the EILs. ChCl with ethylene glycol gave the highest absorption capacity of 0.57 mg/g of the SO2 was absorbed compared to ChCl with glycerol as well as with urea. The use of EILs as an absorbent are a promising method for SO2 capture. Â© Published under licence by IOP Publishing Ltd.